The Use of Individual Fitness Programs According to the Body Types of High School Girls As Means of Increasing Physical Activity - Lyudmila Vashchuk; Nina Dedeluk; Elena Tomashchuk; Olga Roda; Zhanna Mudryk (Lesya Ukrainka Volyn National University, 2017)
The actuality of the problem is caused by the necessity of the use of fitness as means of increasing physical activity at the educational institutions. The introduction of the newest pedagogical technologies is known to enable us to solve different problems of the individual oriented study, formation of the individual educational aspect. The methods of the research of the revelation of initial psychoemotional and morphofunctional state of the high school girls were questioning, testing, medical investigation. The results of the research. Fitness programs based on the recreative kinds of gymnastics considering the age, health state, the level of the physical development and motivational interests of high school girls. To solve the tasks of the correction of сonstitution, increase or decrease of some body parts fitness programs aimed at weight lifting were offered. During the pedagogical experiment the quantity of the respondents with a high level of physical activity increased by 54,7 %. The level of physical preparation (Р < 0,001) improved according to their endurance, strength, flexibility, agility. Conclusions. The improvement of the theoretical explanation and experimental testing of the methods of making individual fitness programs for high school girls considering their morphofunctional peculiarities, motivation and the high school girls' body types in the process of doing physical exercises independently as a constituent part of health protection competence was emphasized. The importance of the received results defining the aspects of the development of the scientific approaches according to the chosen course in the future should be noted.